2020
DOI: 10.1111/1750-3841.15094
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid–based materials encapsulating carvacrol obtained by solvent casting and electrospinning

Abstract: Polylactic acid (PLA) dissolved (15 wt.%) in ethyl acetate (EtAc): dimethyl sulfoxide (DMSO) binary systems (0:1; 1:3, and 2:3 v/v) was used as carrier to obtain carvacrol (CA)-loaded (20 wt.% with respect to PLA) matrices by electrospinning, in comparison with solvent casting. Field emission scanning electron microscopy (FESEM) observations showed that CA-loaded electrospun fibers were thinner than the CA-free ones, and their encapsulating efficiency (EE) increased when EtAc was present in the solvent. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Meanwhile, Tampau et al. (2020) observed that the incorporation of carvacrol at 20 wt% in a PLA solution resulted in thinner fibers than those obtained without AA (Tampau et al., 2020).…”
Section: Polymer Processing Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, Tampau et al. (2020) observed that the incorporation of carvacrol at 20 wt% in a PLA solution resulted in thinner fibers than those obtained without AA (Tampau et al., 2020).…”
Section: Polymer Processing Methodsmentioning
confidence: 99%
“…Regarding the solvent, Tampau et al. (2020) reported that the amount of carvacrol increased from 52% to 68% in PLA nanofibers when ethyl acetate/DMSO 2:3 was used instead of DMSO. This fact was attributed to the lower boiling point of the ethyl acetate that increased the solvent evaporation rate and enhanced the solidification of the fibers, entrapping the AA and preventing its evaporation (Tampau et al., 2020).…”
Section: Polymer Processing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 PLA and its compounds can be used in wide commodity and engineering applications due to its good mechanical, physical, and thermal properties. 36 In this context, PLA could also be employed for the production of nanofibers through electrospinning process with the potential use in the fields of tissue engineering, 7–11 drug delivery, 1215 pH indicator, 16,17 filtration, 18,19 separation, 20,21 sensor application, 22 and food packaging. 23,24…”
Section: Introductionmentioning
confidence: 99%